THE DISPROPORTIONATION OF GOLD(I) CHLORIDE COMPLEXES AT 25 TO 200OC - Gammons C.H.; Yunmei Y.; Williams-Jones A.E. (My University, 1997)
The disproportion of aqueous Au(I) chloride complexes at elevated temperature has been investigated experimentally using the solubility method. At 300°C, the dominant gold species in aqueous HCl solutions is AuCl-2. Upon cooling, this aurous complex partially decomposes according to the following reaction: 3AuCl-2 = 2Au(s) + AuCl-4 + 2Cl- (A1) Log KA1 values were obtained at 100°C (4.42 +/- 0.22), 150°C (2.86 +/- 0.12), and 200°C (1.45 +/- 0.19). The results are in excellent agreement with the earlier potentiometric study of Nikolaeva et al. (1972) at 25-80°C. The combined data were used to obtain the following polynomial: log KA1 = -13.55 + 8593/T - 700610/T2 (T = Kelvin, valid from 25 to 200°C).The rate of reaction (A1) at 25°C was investigated by monitoring the production of AuCl-4 after quench using a UV spectrophotometer. The rates were very slow for the first 5-10 min, but then rapidly increased to values that remained approximately constant with further reaction progress. The measured reaction rates fell in the range 2.1 . 10-8 to 3.7 . 10-6 moles AuCl-4 . kg H2O-1 . minute-1. In general, faster rates were obtained for samples with high initial AuCl-2 concentrations. Addition of gold foils caused an abrupt increase in rate, indicating that the reaction is catalyzed by the native metal. Gold crystals formed during the disproportionation reaction at 25°C show a variety of morphologies, including examples with anomalous fivefold symmetry.Our results indicate that the stability of AuCl-2 relative to AuCl-4 increases quickly with temperature. At 25°C, AuCl-4 is unlikely to be of geochemical importance, with the possible exception of oxidized, acidic solutions that are also rich in chloride ion. In contrast, AuCl-2 may be the dominant form of dissolved gold in brines with near-neutral pH (e.g., seawater), as well as hydrothermal fluids that are both saline and oxidized. Cooling or dilution of solutions saturated with AuCl-2 could result in deposition of Au via a disproportionation reaction, as in our experiments.